2010
DOI: 10.1039/c0an00540a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and discrimination of simvastatin-induced structural alterations in proteins of different rat tissues by FTIR spectroscopy and neural network analysis

Abstract: Statins are commonly used to control hypercholesterolemia and to prevent cardiovascular diseases. Among the statins, Simvastatin is one of the most frequently prescribed statins because of its efficacy in reducing LDL lipoprotein cholesterol levels, its tolerability, and its reduction of cardiovascular risk and mortality. Conflicting results have been reported with regard to benefits (pleiotropic effects) as well as risks (adverse effects) of simvastatin on different soft and hard tissues. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 72 publications
1
19
0
4
Order By: Relevance
“…Protein secondary structure was predicted using NNs based on amide I band between 1700 and 1600 cm −1 . In recent years, this method has been effectively applied to determine protein secondary structure in biological systems (Akkas et al., 2007; Bozkurt et al., 2010; Garip et al., 2010). Amide I band was preprocessed before applying to the NNs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein secondary structure was predicted using NNs based on amide I band between 1700 and 1600 cm −1 . In recent years, this method has been effectively applied to determine protein secondary structure in biological systems (Akkas et al., 2007; Bozkurt et al., 2010; Garip et al., 2010). Amide I band was preprocessed before applying to the NNs.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study (Petibois et al., 2006) showed that there is no significant difference in the analytical performance between FT‐IR and other analytical techniques including biochemical measurements, which require an extensive use of chemical reagents. Its application was reported on the evaluation of the changes in macromolecules such as proteins, both qualitatively and quantitatively (Akkas et al., 2007; Cakmak et al., 2003; Garip et al., 2010; Surewicz et al., 1993). The use of FT‐IR as a novel method was proposed to monitor lipid peroxidation to support biochemical tests (Severcan et al., 2005b).…”
mentioning
confidence: 99%
“…Quando um paciente necessita de estatina para a prevenção ou tratamento da doença coronariana, o mé-dico deve prescrever tal medicamento, mesmo que haja doença hepática crônica ou história pregressa de hepatopatia aguda (38). No entanto, quando os níveis de tran-saminases estão acima de três vezes o limite superior da normalidade antes do início do tratamento, deve maior prudência, sugerindo a investigação da causa da doença hepática antes de prescrever uma estatina.…”
Section: Resultsunclassified
“…As sinvastatinas, por sua vez, são estatinas hábeis em aumentar a atividade da fosfatase alcalina, nível de expressão da osteocalcina e deposição de minerais em células humanas, que seria um efeito benéfico (38). Algumas pesquisas mostraram que estes medicamentos podem estimular a formação óssea, verificada devido ao aumento da atividade da fosfatase alcalina, um efeito anabólico sobre o tecido ósseo pelo aumento da diferenciação dos osteoblastos (40,41).…”
Section: Resultsunclassified
“…For example, neural networks based on Amide I band located between 1700 and 1660 cm −1 in infrared spectroscopy offers new computational approach that has served as a reliable alternative method for predicting protein secondary structure in recent years [19,20,40,41]. This approach has been also successfully applied to proteins of biological tissues and membranes [1,2,12].…”
Section: Discussionmentioning
confidence: 99%